Privacy Enhancing Technologies (PETs) for connected vehicles in smart cities. Issue 10 (18th November 2020) - Safa, Nader Sohrabi; Mitchell, Faye; Maple, Carsten; Azad, Muhammad Ajmal; Dabbagh, Mohammad
Abstract: Many Experts believe that the Internet of Things (IoT) is a new revolution in technology that has brought many benefits for our organizations, businesses, and industries. However, information security and privacy protection are important challenges particularly for smart vehicles in smart cities that have attracted the attention of experts in this domain. Privacy Enhancing Technologies (PETs) endeavor to mitigate the risk of privacy invasions, but the literature lacks a thorough review of the approaches and techniques that support individuals' privacy in the connection between smart vehicles and smart cities. This gap has stimulated us to conduct this research with the main goal of reviewing recent privacy‐enhancing technologies, approaches, taxonomy, challenges, and solutions on the application of PETs for smart vehicles in smart cities. The significant aspect of this study originates from the inclusion of data‐oriented and process‐oriented privacy protection. This research also identifies limitations of existing PETs, complementary technologies, and potential research directions. Abstract : We have investigated possible approaches that help us to improve privacy protection in smart cities and connected vehicles. These techniques have been divided into data‐oriented approaches, process‐oriented approaches, and privacy protection in the Internet of Things. This research also identifies limitations of existing Privacy Enhancing Technologies (PETs), complementary technologies, and potential research directions.